A Note on Smooth Points in Orlicz Sequence Spaces - WANG Jing; CUI Yun-an (Journal of Harbin University of Science and Technology)
In this paper，when φ( u) /u→A( u→∞ ) the criterion of smooth points in Orlicz sequence space generated by general Orlicz functions and the equivalence conditions of smooth points with very smooth points and strong smooth points are given. On this basis，the sufficient and necessary conditions for smooth points in Orlicz sequence space are derived，so that the criterion of smooth points in Orlicz space can be solved.